Pengaruh Kepercayaan Dan Kemudahan Terhadap Keputusan Pembelian Secara Online Di Aplikasi Lazada - Laili Dimyati; Venny Mellandhia Shandy; Gita Cahayani (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2024)
This study aims to determine the influence of trust and convenience on online purchasing decisions in the Lazada application. The research method used is an associative research type. Primary data was obtained from questionnaires distributed to 51 respondents who shopped on the Lazada application or who had the Lazada application. The indicators used were obtained from research, namely the dimensions of Trust (X1), Ease (X2) and Purchase Decision (Y). From the results of multiple linear regression analysis obtained from the variable Trust (X1) of 0.555 and Ease (X2) of 0.408. This shows that all variables X (Trust and Convenience) havea unidirectional influence on variable Y (Purchasing Decisions). From the results of the hypothesis test, namely the influence of the variables Trust (X1) and Convenience (X2) on Purchase Decisions (Y), the value is sig = 0.000, because the sig value = 0.000 <0.05 means that there is an influence of trust and convenience on online purchasing decisions in the Lazada application. Based on this statement means that Ha can be accepted.